Folding: an approach to enable program understanding of preprocessed languages - Kullbach, B.; Riediger, V. (Proceedings Eighth Working Conference on Reverse Engineering, 2001)
Since the early days of programming, preprocessors have been used to increase the expressiveness of programming languages. As a prominent example, the C Preprocessor cpp even allows low level configuration management through conditional compilation. But preprocessors significantly complicate the task of program understanding because "what the user sees is not what the compiler gets". There is a need for bridging the gap between preprocessor input and preprocessor output. The authors propose the use of folding for explicitly representing preprocessor replacements within a program understanding environment. The approach presented has been implemented as part of the GUPRO program understanding workbench. The user is enabled to individually choose the level of detail from the programmer's view to the compiler's view on the source code.